Social Education in The Perspective of the Quran and Hadith - M Farid Yudha Bahari; Achmad Saefurridjal; Iskandar Mirza (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study examines social education contained in the Al-Qur'an, especially surah Ali Imran verse 64 and in the hadith. The research method used in this research uses the library research method, namely an effort to obtain data in the literature. The approach used in this research is also qualitative research, namely a research procedure that produces descriptive data in the form of written or spoken words of a character. .Because this research discusses interpretation in one theme, this research also uses the maudhu'i (thematic) method. Meanwhile, there are two data sources used, namely primary data sources and secondary data sources. The primary data sources used are two classic tafsir books by At Thabary and Ibnu Katsir and two contemporary tafsir books by Hamka with his tafsir Al Azhar and Qurash Shihab with his tafsir Al Misbah and the hadith of Muslim history number 2699. There are at least three things conveyed in the surah Ali Imran verse 64 and HR Muslim number 2699, namely the values ​​of monotheism, unity, and testimony of obedience to the one and only Allah. This verse confirms our worship of the only God, namely Allah SWT. Then continue with an attitude of unity even if some of us turn away. And the Muslims are a testimony that they are people who surrender.